Interlimb force coordination in bipedal dance jumps: Comparison between experts and novices - Shih, H. J. S.; Jarvis, D. N.; Mikkelsen, P.; Kulig, K. (Journal of Applied Biomechanics, 2018)
Bipedal tasks require interlimb coordination that improves with practice and acquisition of skills. The purpose of this study was to compare interlimb force coordination during dance-specific rate-controlled consecutive bipedal jumps (sautés) between expert dancers and nondancers. To analyze coordination of vertical ground reaction forces recorded under each leg, the vector coding approach was used. Although there were no differences in the patterns of interlimb force coordination between groups, the dancers exhibited less variability of interlimb force coordination during the transition phase from weight acceptance to propulsion as well as during the propulsion phase itself. The interlimb force coordination variability was associated with task performance only during the transition phase, which highlights the potential importance of control during this phase. In conclusion, expert dancers were better at reducing interlimb force coordination variability during the task-relevant transition phase, which was related to better performance at maintaining jump rate and jump height consistency.